DIAKONIA: PELAYANAN KASIH BAGI KAUM DISABILITAS - Maeja, Jhon Daeng (STIPAS Keuskupan Agung Kupang, 2024)
Ministry in the church has evolved since the first time the church was founded. This service brings benefits to many people. But the problem is that the church only stops at ministry. There has been no effort to empower those served. Though there are three forms of diakonia are charitative, reformative and transformative. The purpose of this study is to find the form of church service to people with disabilities. The method used is literature review or library research. The result is that there are several ways to provide services to people with disabilities. These include shouting, men-women cooperation, social media campaigns and filmmaking. The conclusion of the study is that reformative and transformative diakonia can be used to help people with disabilities.